COMPARATIVE STUDY OF ANTIOXIDANT ACTIVITIES OF CULTIVATED AND WILD GANODERMA LUCIDUM (W. CURT. FR.) P. KARST APHYLLOPHOROMYCETIDEAE FROM NORTH WESTERN INDIAN HIMALAYAS - K. K. MISHRA; R. S. PAL; R. ARUNKUMAR; J. C. BHATT (The Bioscan, 2014)
Ganoderma lucidum is a high value medicinal mushroom. Many active substances with immuno-modulating effects have been isolated from G. lucidum. The fruiting bodies collected from tree trunk of Dalbergia sissoo was identified and isolated using 2.0% Malt-Extract Agar (MEA) medium and mushroom was cultivated over the substrate wheat straw. Fruiting bodies were analyzed for different phytochemicals and antioxidant activities. The findings indicated that cultivated G. lucidum contained higher phenolics (28.27 mg GAE/g dry wt.) in comparison to wild (24.21 mg GAE/g dry wt.) mushroom fruiting body. Results also showed higher radical scavenging activity on DPPH (10-81.21%) and ABTS (29.34-99.45%), FRAP (98.17-382.01), total antioxidant activity (167.24- 375.74), reducing power (0.10-0.40) and metal chelating activity (39.37-75.0%) in cultivated isolate. All the activities were found to be increased with increase in concentration both in cultivated and wild G. lucidum. In general cultivated isolate had higher antioxidant activities in comparison to wild one.